The Awareness Status of Pregnant Women about Obstetric Danger Signs - Fulya Gökdemir; Tülay Yılmaz; Hüsniye Dinç; Sevda Korkut (Dokuz Eylul University, 2021)
Background: Pregnant women who notice signs of obstetric danger at an early stage contribute to saving lives of both themselves and fetus by applying to health facility more quickly. Objectives: Present study was carried out to determine awareness of pregnant women about danger signs which might occur during pregnancy and related factors. Methods: Data of cross-sectional study were collected by use of a survey between April - September 2018. Sample included 350 pregnant women applying a secondary health institution. Data were analyzed by descriptive statistics and chi-square analysis using SPSS 21.0 statistical program. Results: Average age of participants was 29.57 ± 4.7 and 59.7% of them were multigravida. First 10 symptoms marked as "danger sign" by pregnant women were respectively having contraction or fainting strokes (88.6%), loss of consciousness (88.3%), bleeding from the reproductive organs (86.9%), hypertension (82.3%), fever (81.1%), wound, herpes, wart, pruritus or foul smelling discharge in genitals (78.3%), decrease in frequency of baby movements (78.0%), shortness of breath/ cyanosis (75.7%), ache or irritancy while urinating (71.1%), and changes in vision (69.4%). Sociodemographic and obstetric characteristics and education on obstetric danger symptoms were related with symptoms that pregnant women defined as danger signs. Conclusions: While pregnant women's rates of receiving antenatal care were sufficient, their awareness of in terms of danger signs during pregnancy was not at desired levels and they needed to training in some areas. While presenting these trainings, it is recommended to consider socio-demographic and characteristics of pregnant women.